Optical Properties of Sol-Gel Nb2O5 Films with Tunable Porosity for Sensing Applications - Rosen Georgiev; Biliana Georgieva; Marina Vasileva; Petar Ivanov; Tsvetanka Babeva (Advances in Condensed Matter Physics)
Thin Nb2O5 films with tunable porosity are deposited by the sol-gel and evaporation induced self-assembly methods using organic template Pluronic PE6100 with different molar fractions with respect to NbCl5 used as a precursor for synthesis of Nb sol. Surface morphology and structure of the films are studied by Transmission Electron Microscopy and Selected Area Electron Diffraction. The optical characterization of the films is carried out through reflectance spectra measurements of the films deposited on silicon substrates and theoretical modeling in order to obtain refractive index, extinction coefficient, and thickness of the films. The overall porosity of the films and the amount of adsorbed acetone vapors in the pores are quantified by means of Bruggeman effective medium approximation using already determined optical constants. The sensing properties of the samples are studied by measuring both the reflectance spectra and room-temperature photoluminescence spectra prior to and after exposure to acetone vapors and liquid, respectively. The potential of using the studied mesoporous Nb2O5 films for chemooptical sensing is demonstrated and discussed.